Efecto del protocolo de refrigeración y de congelación sobre la calidad del semen criocongelado de machos cabríos - Durá, Anabel (2024)
The cryopreservation of goat semen plays a crucial role in animal breeding and conservation programs. However, during the freezing and thawing process, the quality of the semen can be affected due to the sensitivity of spermatozoa to low temperatures and changes in cellular structure. In this study, we evaluated the effects of different cooling and freezing protocols on the quality of frozen-thawed goat semen, some using more sophisticated infrastructures and others using simpler methods. Specifically, the aim was to determine the optimal protocol for cooling and freezing goat semen that would result in the highest quality of thawed semen. The semen samples were subjected to cooling at a constant speed in a programmable water bath at 4°C or at a variable speed in a beaker, and then frozen using a programmable freezer or a method involving a Styrofoam box with straws suspended 3 cm above liquid nitrogen. Subsequently, the frozen semen was thawed, and its quality was evaluated using computer-assisted semen analysis (CASA) and membrane integrity assessment by cytometry. The results of the statistical analysis showed no significant differences between the treatments. This indicates that, in this particular study, the different cooling and freezing protocols did not have a significant impact on the quality of the thawed semen, and thus any of them can be used depending on the availability of resources and equipment in each laboratory. With the different protocols studied, similar in vitro semen quality is obtained, enabling its use in the creation of genetic resource banks to conserve genetic diversity in goat populations. However, further research is needed to determine if in vivo fertility is also similar among the different protocols.